Chronic kidney disease as an age related disease: new study perspectives fron animal models to hospitalized patents - La Russa, Daniele; Cerra, Maria Carmela; Pellegrino, Daniela; Montesanto, Alberto (My University, 2019)
Chronic kidney disease (CKD) is a major public health problem worldwide and its main consequences include the loss of renal function leading to end-stage renal disease (ESRD), an increased risk of cardiovascular disease (CVD), a significant increase in morbidity and mortality, and a decrease in health related quality of life. The risk of CKD increases with age, though there seems to be a complex relationship between ageing and this disease: elderly patients are overrepresented in the dialysis population and geriatric complications are highly detectable in younger patients with ESRD. This has led to the hypothesis of a premature biological ageing process of different organ systems associated with CKD. The present research work was based on translational approach to study the role of many CKD risk factors such as hypertension, oxidative stress/inflammation, obesity, and hyperuricemia with the aim of identifying new molecular mechanisms of kidney damage to prevent it by successful behaviour modifications. For this purpose, both human and animal models were used. Human pathological models: in both ESRD and obese patients, the role of oxidative stress, inflammation and hyperuricemia in progression and complications of CKD was investigated. Human physiological models: in a consistent healthy population, the oxidative status and its correlation with traditional cardiovascular risk factors were examined. In addition, the health history data of centenarian subjects was utilized to study the clinical and prognostic value of traditional cardiovascular risk factors in relation to mortality. Animal models: the mechanisms renal damage, induced by hypertension (Spontaneously Hypertensive Rat) and obesity (Cafeteria diet rats), were verified. In this context, the antioxidant and cytoprotective effects of a nutraceutical (Bergamot extract) on obesity was also tested. This multilevel approach has allowed us to individually and synergistically analyze some aspects of the complex pathogenic mechanism of CKD, in order to clarify the role of the new amplifying risk factors for CKD and to prepare an effective personalized prevention plan by acting on both modifiable and non-modifiable risk factors.
Scuola di Dottorato in Scienze della Vita. Ciclo XXXI
Keywords: kidney diseases in old ageGeriatric neophrology; Geriatric neophrology